1988
DOI: 10.1063/1.341646
|View full text |Cite
|
Sign up to set email alerts
|

A novel organic electro-optic crystal: 3-(1,1-dicyanoethenyl)-1-phenyl- 4,5-dihydro-1H-pyrazole

Abstract: Details are given of a new organic electro-optic crystal, 3-(1,1-dicyanoethenyl)-1-phenyl-4,5-dihydro-1H-pyrazole, having a reduced half-wave voltage of 370 V (approximately 8 times lower than lithium niobate). The molecular design, synthesis, and molecular characterization of this compound are outlined and a description is given of growth of 1-cm dimension crystals. These crystals have been characterized in terms of their structure, linear optical properties (refractive index, orientation of optical axes, abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 9 publications
1
33
0
Order By: Relevance
“…33 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 prompted us to detailed quantum chemical calculations of these molecules and the verification of configurational transitions using the X-ray spectroscopy. Similarly to DCNP molecule the structure of (E)-3-(4-nitrostyryl)-1-phenyl-4,5-dihydro-1H-pyrazole is another example of the NLO push-pull type chromophore in which a single nitro group is located in the para position of an aromatic ring constituting an electronacceptor group.…”
Section: Physicochemical Properties and Crystal Structures Of Py-pno mentioning
confidence: 99%
“…33 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 prompted us to detailed quantum chemical calculations of these molecules and the verification of configurational transitions using the X-ray spectroscopy. Similarly to DCNP molecule the structure of (E)-3-(4-nitrostyryl)-1-phenyl-4,5-dihydro-1H-pyrazole is another example of the NLO push-pull type chromophore in which a single nitro group is located in the para position of an aromatic ring constituting an electronacceptor group.…”
Section: Physicochemical Properties and Crystal Structures Of Py-pno mentioning
confidence: 99%
“…The works by Miniewicz et al 8 , Allen et al 7 and Black et al 1 ω ω ω χ − ZZZ =20.86 pm/V. It seems that the DCNP molecule is very sensitive to the environmental effect and the crucial role is played by the multipolar interactions.…”
Section: Introductionmentioning
confidence: 97%
“…The DCNP compound crystallizes in the monoclinic Cc space group 6 and special, noncentrosymmetric arrangement creates the material with large linear electro-optical response (the Pockels effect), whose diagonal Pockels tensor component r 333 is equal to 8.7 10 -11 m/V at 632.8 nm 7 . The works by Miniewicz et al 8 , Allen et al 7 and Black et al 1 ω ω ω χ − ZZZ =20.86 pm/V.…”
Section: Introductionmentioning
confidence: 99%
“…One such material (DCNP) has recently been described. (8) In this organic crystal, all the molecules lie parallel to each other. The crystal symmetry of DCNP is m, so that the crystal is biaxial.…”
Section: Organic Crystalline Electro-optic Materialsmentioning
confidence: 99%
“…It can be shown that the coefficients of the quadric (6) transform in the same way as those of the tensor Sij. Under an appropriate transformation the quadric can be referred to the principal axes described above, and it then has the simplified form (7) By comparing this with the standard equation for an ellipsoid: (8) it can be seen that the semiaxes of the representation quadric are oflengths 1/ V Sl, I/VS2 ,I/VS3 • The refractive indices of an anisotropic material are not in fact the components of a tensor, but are related to the principal components of the impermeability tensor by (1/ n;) = K;; (9) Their values, for any given direction of propagation of light through a material, can be found with the help of the optical indicatrix, which is another name for the representation quadric of the impermeability tensor. Rewriting Eq.…”
Section: Optical Propertiesmentioning
confidence: 99%